TEST ANXIETY LEVEL, SOCIAL ACTIVITIES AND UTILIZATION OF COUNSELLING SERVICES AMONG THE STUDENTS WHO WILL TAKE THE UNIVERSITY ENTRANCE EXAM - (:unkn) unknown (NOBEL ILAC, 2017)
Objective: In Turkey going on with the higher education, it is required to be successful in an annual university Student Selection and Placement Exam (OSYS) for the Turkish Universities which 2/3 of the candidates is disqualified and lost his high education occasion. These difficult requisites may establish anxiety with the students. To measure this test performance focused anxiety of the students who are near to university entrance exam and to evaluate the relationship between the anxiety level and sex, age, living area, living with the family, the graduated high school type, number of the attended university entrance exams, to be succeeded in the exam previously, regular attendance to the preparing courses, involving in social activities and using counselling services are aimed in this study. Besides, to give feedback to the psychological consultancy services and to support the students by giving feedback to reduce their anxiety. Materials and Method: This cross-sectional study includes 254 students who take preperation courses for the Student Selection and Placement Exam (OSYS) in two private courses. Questions about socio-demographic characteristics and Test Anxiety Scale were applied under supervision, chi-square and student-t tests were applied for analysis. Results: Boys were 76% of the 254 participants and the mean age was 18.0 +/- 1.3. Anxiety level of 28.8% of participants was low, 52.4% was medium and 18.8% was high. Among the girls, the students who took the entance exam before, who were irregular, who didn't join social activities and who never or a few use consultancy services courses were more anxious. We found low test anxiety with the students who join the courses regularly, who join social activities at least 2 hours a week and makes use of the consultancy services (respectively chi(2)=5.68, chi(2)=4.03, chi(2)=5.07, p=0.02, p=0.04, p=0.02). Conclusion: Though anxiety level was low with the students who use counseling services, medium and high anxiety level in 71.2% of the participants made us to think that psychological counseling services must be disseminated and especially must be aware of the students who have high test anxiety and remind them the positive effect of social activities and counselling.
Keywords: Test anxiety; student; university; student selection exam; risk factors; TRAIT ANXIETY